Effects of microbial agents on cadmium uptake in Solanum nigrum L. and rhizosphere microbial communities in cadmium-contaminated soil - You, Meng; Wang, Li; Zhou, Guopeng; Wang, Yikun; Wang, Kai; Zou, Rong; Cao, Weidong; Fan, Hongli (Frontiers in Microbiology, 2023)
Solanum nigrum L. (S. nigrum) and microbial agents are often used for the remediation of cadmium (Cd)-contaminated soil; however, no studies to date have examined the efficacy of using various microbial agents for enhancing the remediation efficiency of Cd-contaminated soil by S. nigrum. Here, we conducted greenhouse pot experiments to evaluate the efficacy of applying Bacillus megaterium (BM) along with citric acid (BM + CA), Glomus mosseae (BM + GM), and Piriformospora indica (BM + PI) on the ability of S. nigrum to remediate Cd-contaminated soil. The results showed that BM + GM significantly increased the Cd accumulation of each pot of S. nigrum by 104% compared with the control. Application of microbial agents changed the soil microbial communities. Redundancy analysis showed that the activities of Catalase (CAT) and urease (UE), soil organic matter, available N and total Cd were the main influencing factors. By constructing the microbial co-occurrence networks, the soil microbe was divided into four main Modules. BM + GM and BM + PI significantly increased the relative abundance of Module#1 and Module#3, respectively, when compared with the control. Additionally, Module#1 showed a significant positive correlation with translocation factor (TF), which could be regarded as the key microbial taxa. Further research found that Ascomycota, Glomeromycota, Proteobacteria, and Actinobacteria within Module#1 were also significantly correlated with TF, and these key species enriched in BM + GM. Overall, our findings indicate that the BM + GM treatment was the most effective for the remediation of Cd pollution. This treatment method may further affect the rhizosphere microbial community by affecting soil indicators, which might drive the formation of Module#1, thus greatly enhancing the Cd remediation capacity of S. nigrum.